The Encyclopaedia of Flower Remedies : The Healing Power of Flower Essences From Around the World - Harvey, Clare G. and Cochrane, Amanda (London Thorsons, 1995)
A guide to all the essences available worldwide, from the well-known Bach remedies to the newly available Amazonian and Australian bush essences, in A-Z form. It includes an introduction to the remedies that would be useful to the beginner and therapist alike.
Include Index and Illustration
Keywords: Naturopathy -- Aromatherapy -- Essences and essential oils--Therapeutic use